Community based syphilis screening: feasibility, acceptability, and effectiveness in case finding. Issue 3 (27th May 2005) - Lambert, N L; Fisher, M; Imrie, J; Watson, R; Mercer, C H; Parry, J V; Phillips, A; Iversen, A; Perry, N; Dean, G L
Abstract : Objectives: To investigate the feasibility and acceptability of implementing community based syphilis screening using different sample collection techniques, and its effectiveness in screening at-risk populations and identifying new syphilis cases. Methods: Two phases of syphilis screening were conducted in venues frequented by men who have sex with men (MSM). Phase 1 used venepuncture and phase 2 a validated saliva test. Evaluation used quantitative data from testers, venues and the local genitourinary medicine (GUM) clinic, and qualitative data from venue and programme staff. Results: 1090 MSM were tested over 7 weeks. 62% of testers had not attended a GUM clinic in the past year. 64% of testers reported ⩾2 sexual contacts in the past 90 days and 11% reported ⩾10. Similar diagnosis rates were recorded for phase 1 (1.4%) and phase 2 (1.8%). There was greater uptake of testing with the saliva test in saunas during phase 2. Conclusions: Syphilis screening in gay venues is feasible and acceptable to at-risk MSM, and reaches a group not routinely accessing GUM services. The low case detection for syphilis suggest this approach, while unlikely to contain outbreaks, may be more useful if combined with screening for other sexually transmitted infections and effective health promotion strategies.